2021
DOI: 10.1186/s13052-021-01112-6
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing reveals POLR3B variants associated with progeria-related Wiedemann-Rautenstrauch syndrome

Abstract: Background Wiedemann-Rautenstrauch syndrome (WRS) is a rare autosomal recessive neonatal progeroid disorder characterized by prenatal and postnatal growth retardation, short stature, a progeroid appearance, hypotonia, and mental impairment. Case presentation A 6-year-old patient, who initially presented with multiple postnatal abnormalities, facial dysplasia, micrognathia, skull appearance, hallux valgus, and congenital dislocation of the hip, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 21 23 34 In 2021, report of pathogenic compound heterozygous variants in POLR3B in a patient with WRS led to further expansion of the genotypic spectrum of this condition. 23 A prior study has also identified a nonsense variant in POLR3GL , a gene encoding another subunit of RNA polymerase III, as being associated with WRS. 22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 23 34 In 2021, report of pathogenic compound heterozygous variants in POLR3B in a patient with WRS led to further expansion of the genotypic spectrum of this condition. 23 A prior study has also identified a nonsense variant in POLR3GL , a gene encoding another subunit of RNA polymerase III, as being associated with WRS. 22 …”
Section: Discussionmentioning
confidence: 99%
“…14 15 18 19 In recent years, the phenotypic spectrum of POLR3-related disorders has enlarged significantly, including severe neonatal and infantile presentations to late onset mild ones. [20][21][22][23][24][25][26][27][28][29][30][31][32] Reports of craniofacial characteristics of individuals with POLR3-related disorders are scarce and include patients with biallelic pathogenic variants in POLR1C, 14 a gene also associated with Treacher Collins syndrome (TCS), as well as patients with Wiedemann-Rautenstrauch syndrome (WRS) associated with biallelic pathogenic variants in POLR3A. 21 However, to this day, there have been no studies specifically dedicated to exploring the craniofacial features in POLR3-HLD.…”
Section: Neurogeneticsmentioning
confidence: 99%
“…Interestingly, several different syndromes relating to mutations in RNA pol III subunits show very heterogeneous phenotypes. This includes POLR3 -related hypomyelinating leukodystrophies ( Lata et al, 2021 ; Yeganeh and Hernandez, 2020 ; Thomas and Thomas, 2019 ), Wiedemann-Rautenstrauch syndrome, a neonatal progeroid syndrome ( Wu et al, 2021b ; Wambach et al, 2018 ; Paolacci et al, 2017 ; Beauregard-Lacroix et al, 2020 ), and cerebellar hypoplasia with endosteal sclerosis ( Terhal et al, 2020 ; Ghoumid et al, 2017 ). Additionally, Brf1 mutations have been shown to be causative for cerebellofaciodental syndrome ( Borck et al, 2015 ; Jee et al, 2017 ; Honjo et al, 2021 ; Valenzuela et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The POLR3A gene encodes the largest subunit of RNA polymerase III (Pol III), forming the catalytic core with POLR3B. Pol III is responsible for the transcription of different kinds of non-protein-coding RNAs, which regulate transcription, RNA processing, and translation ( Sepehri and Hernandez 1997 ; Werner et al , 2009 ; Wu et al , 2021 ). This protein also acts in the proper function of the nucleolus, including ribosome assembly by enhancing 5S rRNA synthesis and protein translation, determining the metabolic state of the cell ( Tiku and Antebi 2018 ; Báez-Becerra et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%